Método educativo para prática do teste do reflexo vermelho no cuidado ao recém-nascido - Lúcio, Ingrid Martins Leite (2008)
In Brazil, the red reflex test used with newborns (NB) has helped prevent Child Blindness with multiprofessional participation, including the nurse’s. In Ceará, teaching and practice in nursing care is object of study, and one aims to use this last one in the area of children ocular health. Believing in the creation and application of an educational technology focused on the practice of the red reflex test and in the care to the NB and that the knowledge of aspects inherent in the red reflex test in children allow the creation of technical-scientific skills, one aimed to evaluate an educational method for the practice of nursing care and, specifically, test it for the nurse development, besides verifying the facilities and difficulties to do it, in the professional’s point of view. It’s an evaluating, quantitative study, developed in a reference maternity situated in Fortaleza, Ceará with assistance nurses, in the neonatal area and in the Nursing Department of Federal University of Ceará from July/2006 through March/2007, subdivided in three phases: preparatory, operational and evaluation, using instruments and specific materials for each one of them. For the red reflex test one used a lantern, a direct ophthalmoscope and a color gradient. The data were presented in tables, charts and graphics through descriptive and inferential statistics. On used, average, qui-square test, Phi test for accordance, Pearson Correlation Coefficient and the test of maximum verosimilarity and, one established a significance level of 5%. 16 nurses participated. Fifteen nurses came from public teaching institutions. Eight had between 1 and 5 years of experience in neonatology. Twelve informed they did not know about ocular problems in NB, 11 did not have access to publications about the theme and 14 showed interests about the RRT. One conducted 240 evaluations, each one composed by 12 items, evaluated as “adequate” or “inadequate”. As to those classified as “adequate”, the minimum sum was 134 (69.7%) and maximum of 192 (100%). As to the absolute value of items conducted properly, no evaluation was composed by less than 6 items. Starting from the 13rd evaluation, the nurses conducted properly 100% of the items. The results of RRT were considered as normal in all evaluations and one noticed the predominance of the orange aspect (the reflex color) in 164 (62.2%) of them. Concerning the gradient identified, one verified an accordance coefficient between the examiners of Phi=4.47 and p=0.0001, when comparing the groups’ results in a general way. Similar data was also found when looking for the correlation between the researcher and the nurses during the evaluations. Nine nurses said the biggest facility is the theoretical approach and the difficulty (12) is the non visualization of leucocory. The data confirm the thesis presented and one judges pertinent to the reproduction the viability of the method proposed, to be developed in other sceneries of child’s health, aiming to increase the number of nurses in this practice and, consequently, their insertion in the prevention of blindness in childhood.